Developing Data-Driven, Sustainable Construction Material Transportation Logistics - Tookey, John; Dhawan, Kamal (MDPI AG, 2025)
Construction logistics is central to optimising site operations and delivery processes, yet the need to meet dynamic site requirements while minimising transport movements presents a persistent challenge. Transport efficiency can be improved through both strategic and operational interventions at the business-unit level. This study examines transport-related distribution practices within the plasterboard supply chain in Auckland, New Zealand, and evaluates opportunities to enhance efficiency using established performance metrics. By integrating supply chain management and circular economy principles through spatial analysis and supply chain modelling, the research demonstrates the potential to achieve up to a three-fold improvement in vehicle capacity utilisation. The operational analysis—focused on general-purpose (non-specialist) transport—is grounded in real-world transport data that extends beyond conventional trip-centricity to capture a broader supply chain perspective. This approach addresses a key methodological gap by empirically validating analytical models in a specific operational context. In addition to quantifying efficiency gains, the study identifies context-specific inefficiencies that constrain construction transport performance and proposes sustainable solutions that extend beyond technological fixes. These include strategic organisational measures for improving fleet management, transport contracting and pricing, collaborative planning across supply chain actors, waste management practices, and collaborative logistics through integrated warehousing. By linking technical analysis with business-oriented insights, the research provides proof-of-concept for practical, scalable strategies for improved construction logistics and wider freight transport efficiency grounded in empirical evidence.
Keywords: 33 Built Environment and Design; 35 Commerce, Management, Tourism and Services; 40 Engineering; 3509 Transportation, Logistics and Supply Chains; 4005 Civil Engineering; 3302 Building; 12 Responsible Consumption and Production; 11 Sustainable Cities and Communities; 12 Built Environment and Design; construction logistics; distribution; freight uber; operational sustainability; reverse logistics; transport efficiency; warehousing